The Changing Boundaries of Sports Journalism in the Digital Era: Technological Disruption, New Actors and Professional Challenges - Rojas-Torrijos, José Luis; Nölleke, Daniel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The boundaries of sports journalism continue to expand as non-traditional actors emerge and proliferate in the digital environment. This outstanding and vital specialist area within the news industry faces increasing pressure from adjacent fields. Amateur sports enthusiasts (bloggers, streamers or influencers) and team media for sports organizations adopt many of the roles and tasks historically attributed to sports journalism and engage in activities that may be perceived and regarded as journalistic by audiences. The arrival of new actors around the journalistic field, the heavy use of social media and its impact on sports consumption patterns, the search for new business models for news organizations, and the disrupting technology that is being explored and applied in sports coverage all require new conceptual approaches to better understand the sports news industry in the digital age. All of these considerations led eighteen authors from nine countries (Greece, Portugal, Spain, United Kingdom, Germany, Austria, Australia, Ireland, and Sweden) to publish their research contributions and broaden the discussion in this MDPI reprint about the current trends in the sports media landscape and the most pressing challenges that sports journalists need to face in the years to come.